Phycocyanin-functionalized black phosphorus quantum dots enhance PDT/PTT therapy by inducing ROS and irreparable DNA damage. (29th June 2021) - Zhang, Wanheng; Yu, Liting; Jiang, Yin; Guo, Changying
Abstract : The novel phycocyanin (PC)-functionalized black phosphorus quantum dots (BPQDs) achieve synergistic photodynamic and photothermic activity by inducing massive ROS and irreparable DNA damage, resulting in increased apoptosis in vitro and tumor eradication in vivo . Abstract : To achieve synergistic photodynamic–photothermic therapy, we fabricate the novel phycocyanin (PC)-functionalized black phosphorus quantum dots (BPQDs) referred as PC@BPQDs through a one-step stirring method. PC@BPQDs are characterized by the feature of possessing both near-infrared (NIR) induced photothermal and photodynamic activity. The PC layer not only effectively alleviates plasma protein adsorption onto BPQDs, but also functionally boosts the photothermal therapy efficiency by enhanced ROS release, resulting in increased apoptosis in vitro . Moreover, PC@BPQDs eradicate tumors with high efficacy and low toxicity in vivo. Thus, PC@BPQDs have a promising potential in future therapeutic implications.